Moving beyond addiction: An attachment theory framework for understanding young adults' relationships with their smartphones. Issue 2 (21st October 2019) - Parent, Natasha; Shapka, Jennifer
Abstract: With the increasingly ubiquitous use of smartphones in modern culture, particularly among young adults, recent research has focused on the behaviors, characteristics, and effects of smartphone use, with the evaluation of addictive features largely dominating work in this area. Given concerns around the application of the medical‐addiction model to such a novel, quasi‐normalized, and potentially functional dependence on smartphones, this paper explores the possibility of an alternative framework for understanding university students' relationships with their smartphones (i.e., that of attachment theory rather than addiction). Thus, this paper includes a review of the current state of the literature on problematic smartphone use and addiction before examining the use of an attachment theory framework to understanding this phenomenon. Specifically, the use of smartphones as attachment targets, characterized by the key features of attachment relationships (i.e., proximity seeking, secure base, safe haven, and separation anxiety), is explored and potential practical and theoretical implications of this approach are discussed. Through conceptualizing young adults' relationships with their smartphones within an attachment theory framework, this paper provides a well‐understood, meaningful, and biologically adaptive model with which to understand some of the alarming behaviors that have emerged alongside increasing rates of smartphone use, such as texting while driving, sleeplessness, and social isolation.